What do we mean by industrial relations? a behavioural science approach - Margerison, C. J. (1969)
The object of this paper is to examine the field of industrial relations from a behavioural science viewpoint, in contrast to the traditional institutional approach. The web of industrial relations has grown quickly, and has become highly complex with the development of industrial society. If we are to understand and exert some control over industrial behaviour, which is a vital part of the total behaviour of society, then it is essential to know what factors influence this behaviour. To this extent it is necessary to be clear as to what we mean by the term industrial relations.
Aim -- Levels of industrial relations -- Examination of the model -- Situational factors -- Interaction factors -- Type of conflict -- Outcome and resolution of different types of conflict -- The function of institutional levels.
Photocopy.
Keywords: Industrial organization; Organizational behavior